The effect of adult coloring (mandala pattern) on pain and anxiety associated with dressing changes in burn patients: A randomized controlled trial - Hamidreza Sadeqi; Kobra Rahzani; Davood Hekmatpou; Siamak Rakei Isfahani (SAGE Publishing, 2024)
Introduction The study investigated the effect of mandala coloring on pain and anxiety associated with dressing changes in burn patients. Method This clinical trial was conducted on 60 patients in two groups. At the beginning of the study [baseline (T1)], anxiety and pain were assessed using the BSPAS and VAS. A mandala pattern with colored pencils was provided to the patients in the intervention group. Each patient was given 30 min to color. Anxiety was measured at the 35th minute (T2). A dressing change was performed and 15 min later, the variables were measured again (T3). The control group received no intervention. Results The mean anxiety at the baseline (T1), 35th minute (T2), and 15 min after dressing changes (T3) in the intervention and control groups were 38.73  ±  5.55, 26.20  ±  6.08 and 28  ±  8.53, and 39.17  ±  4.17, 41.27  ±  3.68 and 41.63  ±  2.97, respectively. Anxiety at T1 was at the same for both groups. The anxiety in the intervention group decreased (P < 0.001) at T2 and T3 and increased in the control group. The mean pain intensity at the baseline (T1) and 15 min after dressing changes (T2) in the intervention group was 8.47  ±  1.432 and 5.9  ±  1.9, respectively, and in the control group was 8.33  ±  0.802 and 8.77  ±  0.626. Pain intensity at T1 was at the same level for both groups. The pain in the intervention group decreased at T2 (P < 0.001), whilst it increased in the control group. Conclusion Mandala coloring can reduce pain and anxiety during dressing changes in burn patients. It can be used as adjuvant treatment. Lay Summary Wound dressing in burn patients is accompanied by pain. This painful experience can lead to wound dressing anxiety in these patients. For this purpose, a study was conducted to check whether coloring before wound dressing can reduce the pain and anxiety of dressing in adults. Two groups of patients were included in the study; before the dressing, one group received a pre-prepared image of mandela designs along with colored pencils and colored the design to their taste. The other group did not receive any intervention. The intensity of pain and the level of anxiety of the two groups were measured before and after the dressing. The results showed that the coloring of the mandela design before dressing reduced the pain and anxiety related to the proceedure.